Effect of monetary policy rate announcements on stock prices in Zambia - Samate, Ireen Nunsa (Research of GSB, 2018)
In many countries including Zambia, stock markets are perceived to be crucial for economic development because of the financial intermediary role that they have assumed in the financial system. Stock markets are sensitive to the arrival of new information, especially those that are macroeconomic like monetary policy announcements. This study sought to determine the extent to which the Lusaka Stock Exchange reacts to monetary policy actions by examining the response of all companies listed on the stock exchange to policy rate announcements, with the exception of ZCCM holdings. The study also aimed to look at the differential response of bank stock returns to policy rate announcements. In order to examine the impact of the policy rate announcement on the Lusaka Stock Exchange, the event study methodology was adopted to analyse data from January 2011 to June 2016. The data was collected from the LuSE daily trading reports and monetary policy publications from the Bank of Zambia. It was found that the policy rate announcement has an insignificant negative impact on stock prices in the event of a policy rate increase and an insignificant positive impact on stock prices when the policy rate is maintained. Similar findings were observed for bank stock prices and non-bank stock prices. The impact of the policy rate on stock prices has important implications for the monetary policy transmission mechanism, risk and investment management strategies of financial market participants, as well as government policy and actions towards financial markets. This study makes a unique contribution to existing literature because it is the only study in Zambia to have measured the impact of monetary policy on stock prices using the event study approach.